Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes - Avelino-Capistrano, Fernanda; Barbosa, Leandro Silva; Takiya, Daniela Maeda (Zootaxa, 2016)
Kempnyia couriae sp. nov. is described from specimens (male, female, and nymphs) collected in Rio de Janeiro State, southeastern Brazil. This species is distinguished from its congeners by the male penial armature, having an elongate gonopore, surpassing the hooks, hooks with penial apex forming a globular membranous structure, and by ventrally curved hooks. Females and a nymph were associated with males using DNA barcoding.